A Casa Padre Toledo no cotidiano e na monumentalização - Luiz Antonio da Cruz (2015)
The House of Padre Toledo is one of the most expressive civil architectonic monuments of the Tiradentes city, the oldest Village of São José. The objective of this work is to analise the architectonic individual with its own construction materials e its spaceality, analyzing it throught at the beginnings of limiar. Introduce the main figure that lived there, padre Carlos Toledo de Correia e Melo, that was born in the Village of São Francisco das Chagas de Taubaté, in the state of São Paulo, he took occupancy of the vicar of the Parish of Santo Antônio. He was a farmer and a gold miner to. Toledo became the leader of the Inconfidência Mineira (The Mineiran Freedom Conspiracy), at the County the of the Rio das Mortes. Since the times that Padre Toledo lived in this house, until the inauguration of the last restoration work, the edification had many uses and each one marked it and let a rich memory of details and several characters. The House of Padre Toledo was a scenarios of many important issues, since of the times of the Vicar Toledo, with the first meeting of the members of the Mineiran Freedom Conspiracy, at the County Seat of the Rio das Mortes, of the meetings of the republicans, been residence, the build of the City House and City Council, house of seminary student and then for religious sisters, until been transformed in museum. Through the architectonic and documental analysis of the house, about its interventions and uses, understand the utilization, the appropriation and the conservation a long of the time. The documental research, iconographic and architectonic permit now a bester comprehensibillity of the build for the social, cultural and historic heritage in the context of urbanite that is in, the city Tiradentes.